Haematological and febrile response to Escherichia coli lipopolysaccharide in 12‐week‐old cockerels of genetically diverse layer lines fed diets with increasing L‐arginine levels. Issue 4 (14th April 2016) - Lieboldt, M.‐A.; Frahm, J.; Halle, I.; Schrader, L.; Weigend, S.; Preisinger, R.; Breves, G.; Dänicke, S.
Summary: Due to its decisive function in the avian metabolic, endocrine and immune system L‐arginine (Arg) is dietary indispensable for chickens. In 12‐week‐old cockerels of two high‐ and two low‐performing purebred layer lines, the effects of increasing dietary Arg on the haematological and febrile response were studied over 48 h after single lipopolysaccharide (LPS) injection. The offered diets contained Arg equivalent to 70%, 100% and 200% of recommended supply. Pathophysiological alterations in weight gain, feed intake, body temperature and differential blood count were examined in comparison with their physiological initial values. Within the first 24 h after LPS injection, cockerels reduced feed intake and lost body weight subsequently. Thereby, low‐performing genotypes lost body weight to a lesser extent than high‐performing ones. The loss of body weight was further intensified by deficient dietary Arg. Within the following 24 h, cockerels recovered by improving feed intake and weight gain. Furthermore, LPS induced genotype‐specific fever response: both brown genotypes showed initial hypothermia followed by longer lasting moderate hyperthermia, whereas the white genotypes exhibited biphasic hyperthermia. Fever response was accompanied by significant changes in differential blood counts. Characterized by lymphopenia and heterophilia, a severe leucopenia was observed from 4 to 8 h after LPS injection and replaced by a marked leucocytosis with longer lasting monocytosis up to 48 h after LPS injection. Under given pathophysiological conditions, deficiently Arg‐supplied cockerels showed higher total leucocyte counts than adequately and excessively Arg‐supplied cockerels. However, deficient and surplus dietary Arg tended to cause higher ratios between heterophils and lymphocytes. To conclude, present results confirmed that LPS induced numerous immunological changes in 12‐week‐old cockerels and emphasized that chicken's genotype is a source of variation to be considered for immunological studies. Deficient dietary Arg intensified acute changes in differential blood counts and weight gain during LPS‐induced inflammation.